It Ain’t Necessarily So: Australian Competition and Consumer Commission v Pfizer Australia Pty Ltd and the Reasons for Reforming s 36 of the Commerce Act - Scott, Paul G (Victoria University of Wellington Law Review, 2020)
The Government has indicated it is going to amend s 36 of the Commerce Act 1986. Its reasons are that s 36 fails to capture sufficient anticompetitive conduct, is difficult and complex to apply and makes litigation unpredictable. The Government proposes a substantial lessening of competition test which it claims will capture more conduct, make analysis more straightforward and provide a source of Australian authority for New Zealand courts. This article uses an Australian Federal Court case, Australian Competition and Consumer Commission v Pfizer Australia Pty Ltd, to show that the claims for reform are overstated and in some cases incorrect. It argues the foundations of the case for reform of s 36 are wobbly and infirm.